AI-Driven Chatbots as Language Tutors: Enhancing Written Proficiency in ESL - Lingaiah, Jayasri; Ishak, Siti Norashikin; Mishra, Pradip Kumar (International Journal of Humanity and Social Sciences, 2024)
Purpose: This research study examines the viability of using Artificial Intelligence chatbots for increasing written performance of ESL students. Methodology: The research employs a secondary qualitative approach, synthesizing existing literature to identify themes on chatbot applications in language learning. Findings: As it was found out, the use of chatbots enables learners to get prompt feedback within a session, which helps in correcting the mistakes made and strengthening the applied language learning and acquisition rules and strategies. However, some of the disadvantages include; lack of ability to differentiate culture when giving feedback and some difficulties in maintaining learner’s attention over a long-term basis. Contribution to Theory, Policy and Practice This study shows the ability chatbots have in decreasing learner anxiety and increasing confidence in writing. It is also noted within this study that additional refinement is needed in AI responsiveness to bring chatbots closer to being contextually and culturally aligned with diverse learners. Hence, the study contributes to the discourse on the implementations of cutting-edge technologies into enhancing written proficiency in ESL and calls for further developments of AI-powered systems to tackle challenges surfaced in the ESL teaching and learning processes.